4'-[2-(2-Ethoxy-ethoxy)eth-oxy]-bi-phenyl-4-carboxylic acid: Correlation between its crystalline and smectic phases - Montani, R.S. (2009)
The crystal structure of the dimeric title compound, C19H 22O5H, is dominated by a head-to-head hydrogen-bonding inter-action between centrosymmetrically related carboxyl groups in each monomer. The result is a dimeric axis of unusual length (ca 34 Å), but still shorter than what could be expected for a fully extended chain, owing to two turning points in the oligo-eth-oxy ends. This allows for an explanation of the structure of the smectic mesophase exhibited by this compound and at the same time fully validates former geometric estimations based on PM3 calculations. © 2009 International Union of Crystallography.